PERANAN GURU PENDIDIKAN AGAMA ISLAM (PAI) DALAM MENGATASI KESULITAN BELAJAR SISWA SEKOLAH DASAR NEGERI 006 SETIANG KECAMATAN PUCUK RANTAU KABUPATEN KUANTAN SINGINGI - Elvi Susanti; Wigati Iswandhiari (Universitas Islam Kuantan Singingi, 2019)
This study aims to determine the role of PAI teachers in overcoming learning difficulties of students at SDN 006 Setiang, Pucuk Rantau District, Kuantan Singingi Regency and the factors that influence it. Data collected in the form of numbers or quantitative data, is enough to use descriptive analysis and visual presentations. The results of this study The role of PAI teachers in overcoming student learning difficulties in 006 Setiang Elementary School in Pucuk Rantau Subdistrict, Kuantan Singingi District is categorized as